Habitat Characteristics and Reproductive Aspects of Olive Ridley Sea Turtles (Lepidochelys olivacea) in Sunur Beach of Pariaman City of West Sumatra Province - Anggi Irfan Hasibuan; Joko Samiaji; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Research has been conducted in the month of June to August 2014 at Sunur Beach of Pariaman City of West Sumatra Province. The purpose of this study was to investigate the characteristics of nesting habitat of sea turtle (Lepidochelys olivacea), fecundity, egg diameter, and hatching numbers associated with the size of the parent turtle. The results showed the characteristics of the nest were as follows: the average nest depth was 37.48 cm, nest diameter was 20.66 cm, the average temperature was 29.92 °C nest surface, the temperature inside the nest was 29.25 oC, sediment texture size 1,55 mm and the distance from the nest highest tide towards the ground 1.80 m. The average length was 67 cm nest, nest an average width was 19.8 cm, the average number of eggs was 105.6, the average diameter was 38.02 mm eggs. The average number of eggs hatching success was 93.33%. Kata Kunci : Lepidochelys olivacea, nesting habitat, reproduction, Sunur Beach